Assessment of Knowledge and Attitudes among Pregnant Women’s Towards Folic Acid in Take during Pregnancy in Al-Diwanyia Governorate - Fadia H. Ali (Journal of Global Pharma Technology, 2018)
Folic acid or folate is a B9 vitamin; it is affect the formation of cells in the fetus.  Objective: Assess the pregnant mothers' knowledge and attitudes towards folic acid during pregnancy and to determine the relationship between their demographic data and (knowledge and attitude).  Methodology: A descriptive design was carried out to assess knowledge and attitudes among pregnant women's towards a folic acid intake during pregnancy in Al-Diwanyia Governorate. A non- probability, purposive sample of (103) pregnant women at Al- Diwanyia Governorate was selected from the mothers who attending for follow up in the antenatal care unit of the gynecology and pediatric teaching hospital. A questionnaire was constructed for the purpose of the study, it was composed of three Likert scale was developed in order to collect the study data that include data related to socio-demographic data, questions related to mothers' knowledge and attitudes. Results: The present study indicate that (72.81 %) of mothers aged between 20-35 years. About half of them had university education(45.63%) and majority of them(85.43 %)  are housewives lived in urban areas (75.72 %) and ( 79.6 %) of them had fair ( insufficient ) knowledge about folic acid as usage, important, dose, and sources and More than half of the studied subjects (71.8 %) were had positive attitudes toward folic acid uses during pregnancy  and there is no statistical significance between mothers' knowledge and any of socio-demographic data except level of education and monthly income are significant at p. value less than 0.05.Conclusion: The pregnant women have fair of knowledge regarding folic acid and its importance during pregnancy and the majority of them had positive attitudes toward  uses of folic acid during pregnancy .Recommendation, developing of educational program for pregnant women to raise their knowledge about folic acid and its important during pregnancy, emerging sessions to explain the important of follow up in pregnancy given to the recent wife.Key words: Assessment, knowledge, attitudes, folic acid.